2016
DOI: 10.1080/1343943x.2015.1128102
|View full text |Cite
|
Sign up to set email alerts
|

Relation between seeding times and stem yield of sorghum in cold region in Japan

Abstract: The seeding time is an important factor affecting the process of stem yield. Nevertheless, details related to the optimum seeding time to maximize the stem yield of sweet sorghum have not been studied. This study elucidated information necessary to ascertain the optimum seeding time to obtain the maximum stem yield. We conducted an examination with three seeding times at intervals of two weeks, ranging from late May to mid-June for four years during 2009-2012, and we analyzed the relation between seeding times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Growth of sweet sorghum in temperate climates Sweet sorghums are not adapted to temperate conditions; however, lately due to the development of photoperiod-insensitive lines, sorghums have been cultivated in temperate regions as well (Thurber et al, 2013). Sweet sorghums have been previously grown in the colder Northern regions of Japan, for stem biomass, with sowing in early to mid-June as ideal for maximum stem yield (Fujii et al, 2016;Nakamura et al, 2011). The period of growth from sowing to flowering in tropical regions is around 55-70 days, with an extension by 20-30 days in temperate conditions (Mocoeur et al, 2015;Rao et al, 2013), which was observed in the varieties grown in our study as well (Tables S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…Growth of sweet sorghum in temperate climates Sweet sorghums are not adapted to temperate conditions; however, lately due to the development of photoperiod-insensitive lines, sorghums have been cultivated in temperate regions as well (Thurber et al, 2013). Sweet sorghums have been previously grown in the colder Northern regions of Japan, for stem biomass, with sowing in early to mid-June as ideal for maximum stem yield (Fujii et al, 2016;Nakamura et al, 2011). The period of growth from sowing to flowering in tropical regions is around 55-70 days, with an extension by 20-30 days in temperate conditions (Mocoeur et al, 2015;Rao et al, 2013), which was observed in the varieties grown in our study as well (Tables S1 and S2).…”
Section: Discussionmentioning
confidence: 99%